PERAN MEDIASI SIKAP HEDONIS DAN UTILITARIAN DALAM MEMPENGARUHI HUBUNGAN KETERLIBATAN AFEKTIF DAN KOGNITIF TERHADAP NIAT BELI PRODUK APPLE - Heni Kusumawati; Anisa Triska Sari (Jurnal Akuntansi Dan Manajemen, 2023)
This study aims to examine the effect of affective and cognitive engagement on purchase intentions on Apple branded products with Hedonic and utilitarian attitudes as mediating factors. The data source applied to this research is primary data. The sample for this research are men and women aged 18 to 50 years who buy Apple branded products on the Java. The number of samples applied was 131 respondents who were selected through actual purposive sampling based on certain criteria. Data collection was carried out by distributing questionnaires online using the Google Form platform. The collected data were analyzed using multiple linear regression methods with the help of SPSS software. Research findings show that affective involvement correlates with Hedonis attitudes of consumer of Apple products, cognitive involvement influence utilitarian attitudes of consumers of Apple products, Hedonic and utilitarian attitudes influence purchase intentions of consumers of Apple products, Hedonic attitudes mediates the relationship between  affective involvement and purchase intentions of Apple products, utilitarian attitudes mediates the relationship between cognitive engagement and purchase intentions of Apple product.